A high pressure La K-edge X-ray absorption fine structure spectroscopy investigation of La1/3NbO3. Issue 1 (2nd January 2018) - Marini, C.; Joseph, B.; Noked, O.; Shuker, R.; Kennedy, B. J.; Mathon, O.; Pascarelli, S.; Sterer, E.
ABSTRACT: La K-edge X-ray absorption spectroscopy has been used to elucidate the changes in the local electronic and lattice structure that occur in the A-site deficient double perovskite La 1 / 3 NbO 3 up to 6 GPa. The pressure evolution of the oxygen dodecahedrum around the A-site has been examined. XANES (X-ray absorption near edge structure) data show modifications ascribed to the increase of bands overlapping as a consequence of the bond distance contraction, which has been directly probed by EXAFS (extended x-ray absorption fine structure) spectra. The La–O Debye Waller factors (DWFs) tend to increase whereas the La–Nb bond DWFs show only a tendency to decrease indicating the robustness of the crystal lattice structure, even in presence of the oxygen disordering. This permits the system to reverse back to its original conditions in this pressure range as evident from the measurements upon pressure release. The present results have been interpreted in the light of charge transfer related to the two-step reduction mechanism acting at the Nb site (with niobium ions passing from Nb 5 + to Nb 4 + ) which also results in the elongation of the Nb–O bond distances in the octahedra, in agreement with the Nb K-edge results reported earlier.